Effect of Qingjie Fuzheng Granules on Proliferation, Apoptosis and Migration of Colorectal Cancer SW620 Cells - Xiaoqin ZHU; Hong YANG; Bin HUANG; Lihui WEI; Jiumao LIN (康复学报)
Objective:To investigate the effects and mechanisms of Qingjie Fuzheng Granules (QFG) on colorectal cancer SW620 cells in proliferation, apoptosis and migration.Methods:Colorectal cancer SW620 cells in vitro were treated with 0,0.5,1 and 2 mg/mL QFG. The inhibitory effect of QFG on cell proliferation was detected by MTT assay after 24 h and 48 h. The morphology of SW620 cells was observed with inverted microscope after 24 h. The cell cycle after 24 h was measured by flow cytometry. Apoptosis of SW620 cells after 24 h was detected by Hoechst 33258 staining test. The migration ability of cells after 0 h,6 h,12 h and 24 h was detected by scratching test. The expressions of Ki-67, MMP-2 and Cleaved-Caspase-3 proteins were detected by Western blot assay after 24 h.Results:(1) In the concentration range of 0,0.5,1,2 mg/mL, QFG significantly reduced the cell proliferation in a time and dose-dependent manner. The differences were statistically significant when compared with the control group in the same time (P<0.05). (2) After treatment with 0.5,1,2 mg/mL QFG for 24 hours, the morphology of the cells changed significantly. With the increase of the concentration, the cell density decreased gradually, the suspended cells increased, and some cells got shrank and rounded. (3) The result of flow cytometry showed that the G1 phase of the QFG group in the 0.5,1,2 mg/mL concentration was decreased, but the S phase was increased and the G2 phase was not significantly changed. The percentage of each period was significantly different from that of the control group (P<0.01), but not dose dependent. (4) The Hoechst 33258 staining results showed that the cell morphological manifestations of apoptosis were more obvious with the increase of QFG concentration. (5) The scratch test showed that QFG in the 0.5,1,2 mg/mL concentration could reduce the migration ability of SW620 cells, and the scratch healing rate decreased gradually with the increase of intervention time and QFG concentration, showing a time and dose-dependent effect. Compared with the control group, the difference of 12 h and 24 h was statistically significant (P<0.01). (6) In addition, compared with the control group, QFG in the 0.5,1,2 mg/mL concentration significantly reduced the protein expression of Ki-67 and MMP-2, increased the protein expression of Cleaved-Caspase-3, and showed a dose-dependent, the difference was statistically significant (P<0.01).Conclusion:QFG can inhibit the proliferation, induce apoptosis and inhibit migration of colorectal cancer SW620 cells, and its mechanism may be related to down-regulation of Ki-67 and MMP-2 protein expression and up-regulation of Cleaved-Caspase-3 protein expression.